Mandibular Phosphaturic Mesenchymal Tumor–Mixed Connective Tissue Variant in a Young Girl. (November 2013) - Luo, Lisa; Low, Nelson; Vandervord, John
Phosphaturic mesenchymal tumor–mixed connective tissue variant (PMTMCT) is an extremely rare tumor associated with tumor-induced osteomalacia. The majority occur in middle age and arise from the extremities. This report describes a young girl with PMTMCT arising in the mandible and with no evidence of paraneoplastic syndrome.